2017
DOI: 10.1108/ejtd-06-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Harmonising training and development across an industry: the case of Australian rail

Abstract: Purpose This paper aims to explore why harmonisation, given its potential, is so difficult to achieve. It analyses the issues and challenges in achieving harmonisation of training and development across an industry. Design/methodology/approach The approach was a meta-analysis of six research projects undertaken in the Australian rail industry. These projects varied in duration from 12-24 months. Between 2009 and 2013, rail employees in varying roles and levels of seniority, including middle managers, front-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…From their research using sector-based case studies in the UK, Felstead et al (2009) argue that any analysis of workplace learning needs to begin with the external and internal features of the productive system within which workplaces sit, including international, national or country-specific regulation and legislation. A recent study by Short and Harris (2017) identified a trend towards harmonisation of company-based training in the Australian railway sector. This echoes findings from research in the field of human resource development (HRD) providing insights from alignment theory into the drivers for convergence between HRD and business strategies (Gibb and Wallace, 2014), including the training strategies of multinational companies (Pilz and Li, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From their research using sector-based case studies in the UK, Felstead et al (2009) argue that any analysis of workplace learning needs to begin with the external and internal features of the productive system within which workplaces sit, including international, national or country-specific regulation and legislation. A recent study by Short and Harris (2017) identified a trend towards harmonisation of company-based training in the Australian railway sector. This echoes findings from research in the field of human resource development (HRD) providing insights from alignment theory into the drivers for convergence between HRD and business strategies (Gibb and Wallace, 2014), including the training strategies of multinational companies (Pilz and Li, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the HRD field, by contrast, the stakes are lower. Studies of HRD harmonisation processes in different organisations and sectors confirm that the value of discontinuous, strategic change, flexibility and managerial discretion is prioritised over process harmonisation and standardisation (Lahiff, et al , 2019; Short and Harris, 2017). This study further confirms that HRD assumptions about the priority of flexibility and responsiveness over the values of consistency and uniformity serve to diminish professional interest in, and imperatives for, standardisation.…”
Section: Discussionmentioning
confidence: 99%
“…Third, organisational excellence theory fails to account for other risk and decision factors that affect performance (Goetsch and Davies, 2014). For example, within the HRD field, studies suggest a reluctance to harmonise organisational-level training and continuous development processes as this is understood as compromising organisational flexibility, change readiness, innovativeness and organisational differentiation (Anderson, 2017;Lahiff et al, 2019;Short and Harris, 2017;Smith et al, 2014).…”
Section: Theorising Standardsmentioning
confidence: 99%
“…The review is based on: “Harmonising training and development across an industry: the case of Australian rail” by Tom Short and Roger McL. Harris (2017).…”
Section: Commentmentioning
confidence: 99%